Low-strain sensor based on the flexible boron-doped diamond-polymer structures. (March 2021) - Rycewicz, M.; Ficek, M.; Gajewski, K.; Kunuku, S.; Karczewski, J.; Gotszalk, T.; Wlasny, I.; Wysmołek, A.; Bogdanowicz, R.
Abstract: A free-standing high boron-doped diamond nanosheet (BDDNS) has been fabricated for the development of a flexible BDDNS strain senor. High boron-doped diamond was initially grown on a tantalum substrate in a microwave plasma-assisted chemical vapor deposition method, and was then transferred to a Kapton polymer substrate to fabricate the flexible BDDNS/Kapton device. Before performing the transfer process, the thin BDDNS's morphology and bonding structure on the top and bottom surfaces were investigated using scanning electron microscopy and Raman spectroscopy. The contact potential difference and work function values of the BDDNS top and bottom surfaces were measured using a Kelvin probe atomic force microscope. Significant electrical conducting properties were observed from the resistance mapping of the BDDNS foil, and the average resistance value of 31 Ω attained from the top surface of the BDDNS foil. The electrical response of the BDDNS/Kapton device was investigated using a custom-made measurement system and a positive residual resistance change with strain was observed. The developed BDDNS/Kapton device was able to sustain for measuring up to 0.55% of strain, which indicates it may have great potential to be utilized in low-strain sensor applications. Graphical abstract: Image 1